Gauging the ethicality of students in Turkish institutions of higher education - Beekun, Rafik I.; Alayoğlu, Nihat; Öztürk, Ali Osman; Babacan, Mehmet; Westerman, James W. (Springer, 2017)
We investigated the ethical behavior of Turkish university students to (a) compare the difference in ethical behavior between business students and non-business students, (b) examine the impact of key contingency variables on how they make decisions when confronted with an ethical dilemma, and (c) investigate the process underlying the ethical behavior of Turkish students. Data were collected from business students (n = 158) at a major private university in Western Turkey. The results indicate that a Turkish student's peers, marital status, and education level exert a significant effect on their ethical behavior. Further, business students specifically differed from non-business students in their enhanced use of egoism when confronted with an ethical dilemma. The results of this research may have important educational policy implications for business ethics in Turkey.
WOS: 000399659100012
Keywords: Business Ethics; Higher Education; Turkey; Education Level; Marital Status; Decision-Making Process